16S rDNA analysis of osteoporotic rats treated with osteoking. Issue 6 (23rd June 2022) - Sun, Yan; Zhang, Hui-Jie; Chen, Ran; Lee, Wen-Hui; Zhao, Hong-Bin
Abstract : Introduction. Osteoporosis (OP) is characterized by microstructural degeneration of bone tissue, low bone mass, bone fragility and even brittle fracture (osteoporotic fracture, OPF). OP and OPF are common and there are many disadvantages to the current medications for OP/OPF. Osteoking is a traditional Chinese medicine (TCM) originating from the Yi nationality (Yunnan, China) that has been used to treat bone diseases for decades. Hypothesis/Gap Statement. This study will reveal the changes in the intestinal microbiota of OP rats after 70 days of osteoking treatment. Method. With duplication of sham and OP rats, eight groups were established, with six rats in each group. The intestinal microbiotas were analysed by 16S rDNA sequencing. Results. The results showed that osteoking changed the intestinal microbiota of sham rats and OP rats. The mechanism by which osteoking improves OP is related to the functions of the intestinal microbiota. After 70 days of treatment with osteoking, the contents of Pseudonocardia, Pedomicrobium, Variovorax, Niastella and Actinosynnema were decreased in OP rats. The functions of the above intestinal microbiota related to iron metabolism affected calcifediol and 25(OH)D, and measuring these bone metabolic indicators is required for further study. Conclusion. Osteoking changes the intestinal microbiota to improve OP, and further study which reveals these intestinal microbiota and mechanism is needed.